Komposisi Motif Batu Bata Pada Baju Kurung Batik - Agreani, Melia; Widdiyanty, Widdiyanty; Hendra, Hendra (Relief : Journal of Craft, 2024)
ABSTRACTComposition Of Brick Motif On Baju Kurung BatikBricks are coarse soil that is processed in such a way as to become bricks. The bricks have a block shape and have a rough texture. In the middle of the brick there are 4 (four) holes, these holes are used for air distribution which functions as drying or reducing the water content contained in the bricks, besides that the bricks also have solid and hard properties. The creation of this work begins with the shape of the stylized bricks on each side of the brick. The shape of this brick is composed as a decorative motif on the baju kurung. The process of creating this work goes through three stages, including the exploration stage, which is to see firsthand the process of making bricks. Design by pouring ideas into the form of a sketch which then becomes the chosen design to the realization of the work through the handmade batik technique and then applied to the baju kurung. Creation uses the theory of form, function, color, motif, stylization and aesthetics. The form of the work created is a size S-sized baju kurung using handmade batik techniques. The function of this baju kurung is as clothing for teenage and adult women who are used during formal events or official events. There were five works, with the titles: “Opposite”, “Complexity”, “Scattered”, “Balance”, “Contrast”, “Repetition” and “Simplicity”.Keywords: batik, bricks, baju kurung and motifs. INTI SARIKomposisi Motif Batu BataPada Baju Kurung BatikBatu bata merupakan tanah kasar yang diolah sedemikian rupa hingga menjadi batu bata. Batu bata memiliki bentuk balok dan bertekstur kasar. Pada bagian tengah batu bata terdapat 4 (empat) lubang, lubang ini digunakan untuk penyalur udara yang berfungsi sebagai pengeringan ataupun pengurangan kadar air yang terkandung di dalam batu bata, selain itu batu bata juga memiliki sifat padat dan keras. Penciptaan karya ini berawal dari bentuk batu bata yang sudah distilisasi pada setiap sisi batu bata. Bentuk dari batu bata ini di komposisisikan sebagai motif hias pada baju kurung. Proses penciptaan karya ini melalui tiga tahapan di antaranya, tahap eksplorasi yaitu melihat secara langsung proses pembuatan batu bata. Perancangan dengan menuangkan ide ke bentuk sketsa yang kemudian menjadi desain terpilih hingga perwujudan karya melalui teknik batik tulis lalu diaplikasikan pada baju kurung. Penciptaan menggunakan teori dari bentuk, fungsi, warna, motif, stilisasi dan estetika. Bentuk karya yang diciptakan adalah setelan baju kurung berukuran S menggunakan teknik batik tulis. Fungsi baju kurung ini sebagai pakaian wanita remaja dan dewasa yang digunakan pada saat acara formal atau acara resmi. Jumlah karya yang dibuat sebanyak lima karya, dengan judul yaitu: “Berlawanan”, “Kerumitan”, “Bertaburan”, “Keseimbangan”, “Kontras”, “Pengulangan” dan “Kesederhanaan”.Kata kunci : batik, batu bata, baju kurung dan motif.